Sustainable urban planning development indicators model for neighbourhoods in Tripoli, Libya - Elgadi, Ahmed Abdulmottaleb (2019)
All developmental and urban planning practices in Libya have been carried out for improving the neighbourhoods sustainability, whilst decreasing their effect on the resources and the natural environment. Hence, a proper understanding of the elements, which contribute to the sustainable urban planning development indicators of neighbourhoods is essential. The aim of this study is to develop a Sustainable Urban Planning Development Indicators (SUPDI) model, focuses on various SUPDI elements such as social, economic, environmental and institutional for a neighbourhoods in Tripoli, Libya. The effect of these elements on perceived personal responsibility towards the adoption of the SUPDI model for neighbourhoods in Tripoli, Libya was also investigated. First step of this research was literature on existing sustainability indicators related to neighbourhoods planning reviewed to identify 46 sustainability indicators that clustered into four elements, which influence SUPDI. These sustainability indicators and assigned elements were validated by 77 practitioners during the pilot study. Secondly, the actual survey was completed by a total of 307 practitioners who tested the validity of the model and the proposed hypotheses. Thereafter, the results were analysed using SPSS and Smart-PLS techniques. The statistical analysis showed that the four elements positively affected the SUPDI and perceived personal responsibility. Furthermore, perceived personal responsibility towards the SUPDI models showed the highest beta value (β = 0.426), followed by the environmental (β = 0.253), social (β = 0.213), economic (β = 0.173), and institutional (β = 0.170) parameters. While examining the validity of the various models, results found that the SUPDI model had a good model fit value of R2 = 0.379. The SUPDI model used in this study very reliable and it could help developers and planners understand the importance of sustainability-related risks seen in neighbourhoods. This could also assist them to further implement and develop more informed and responsible decisions for improving neighbourhood sustainability.